Mobile media methods in gender and (im)mobilities research - Markl, Andrea; Bork-Hüffer, Tabea (Handbook of gender and mobilities, 2024)
This chapter provides a starting point for those who want to research the implications of the entanglements of mobile technologies and media with everyday lives for gender and (im)mobilities. We denote techniques that simultaneously aim at analyzing these entanglements while also applying technologies and media as (mobile) tools of research as ‘mobile media methods.’ Drawing from previous studies, we illustrate the general relevance of mobile media for (research on) gender and (im)mobilities before debating the potentials and challenges of mobile media method(ologie)s related to: the researcher-participant-media relation, entanglements of mobile media in everyday life, negotiations of absence and presence within remote research and the generated multimedia data. The chapter illustrates the dynamics, adaptability and flexibility of the ongoing experimentation with mobile media methods. We end with a call to continue experimenting with these methods to contribute to a better understanding of negotiations of gender and (im)mobilities in mediatized everyday worlds.